2017
DOI: 10.1021/acsnano.7b02035
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Gold Nanoclusters

Abstract: Bulk gold (Au) is known to be chemically inactive. However, when the size of Au nanoparticles (Au NPs) decreases to close to 1 nm or sub-nanometer dimensions, these ultrasmall Au nanoclusters (Au NCs) begin to possess interesting physical and chemical properties and likewise spawn different applications when working with bulk Au or even Au NPs. In this study, we found that it is possible to confer antimicrobial activity to Au NPs through precise control of their size down to NC dimension (typically less than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
442
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 519 publications
(457 citation statements)
references
References 48 publications
14
442
1
Order By: Relevance
“…[6,7] Unlike gold nanoparticles (AuNPs), smaller gold nanoclusters (AuNCs) have recently emerged as innovative nanomedicines with interesting properties,s uch as size-dependent fluorescence. [11] However,studies describing the effect of AuNCs on MDR bacteria are scarce,p articularly for combating MDR bacteria in vivo. [11] However,studies describing the effect of AuNCs on MDR bacteria are scarce,p articularly for combating MDR bacteria in vivo.…”
mentioning
confidence: 99%
“…[6,7] Unlike gold nanoparticles (AuNPs), smaller gold nanoclusters (AuNCs) have recently emerged as innovative nanomedicines with interesting properties,s uch as size-dependent fluorescence. [11] However,studies describing the effect of AuNCs on MDR bacteria are scarce,p articularly for combating MDR bacteria in vivo. [11] However,studies describing the effect of AuNCs on MDR bacteria are scarce,p articularly for combating MDR bacteria in vivo.…”
mentioning
confidence: 99%
“…Gold NPs less than 2nm have shown strong antibacterial activity. 27 It is speculated that the antimicrobial activity of AuNPs reported in some studies may be due to the bactericidal activity of co-existing chemicals not completely removed from AuNPs during synthesis. However, photo thermal therapy (PTT) offers a promising new approach for improving the bactericidal potential of AuNPs.…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%
“…Increased ROS generation under NIR or UV light irradiation and lightenhanced metal-based NPs will be reviewed in the next section. [78] In this study, when the particle size was reduced down to <2 nm, Au NCs were found to display strong antimicrobial activity toward both Gram-positive and Gram-negative bacteria. Compared with Ag and Cu NPs, Au NPs are much more inert and biocompatible, and therefore potentially more promising therapeutic antimicrobial agents.…”
Section: Metal-based Nps Generating Rosmentioning
confidence: 76%